Dialogic essentialism and protecting against stigma within the fat admirer community. Issue 3 (1st September 2020) - Neumann, Elyse
ABSTRACT: Fat Admirers (FAs) represent a group of stigmatized individuals who challenge Western ideals of beauty. Using an internet ethnography, I analyze the sharing of stigmatizing experiences among FAs on the Dimensions forum, an online community for FAs and FFAs (female Fat Admirers). This research explains how individuals shape their understanding of an FA identity and how the use of self-protective strategies promote increased importance, validation, and protection of a stigmatized identity. This research adds to previous work on self-protective strategies against stigma. I argue that a new strategy, dialogic essentialism, is employed. Dialogic essentialism describes the process by which FAs converse with similarly situated others in attempts to normalize their essentialist beliefs, thus protecting against possible stigmatization.